Bimbingan Teknis Kewirausahaan dan Pembuatan Rencana Usaha Jasa Wisata Curug Panganten Kabupaten Bandung Barat - Deddy Saefulloh; Deddy Sobarna Sutaji; Syifaa Novianti; Rikantini Widiyanti; Sherly Raka Siwi Putri Utomo; Dinarsiah Chendraningrum (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2020)
This article was written based on the Bandung State Polytechnic Community Service (PKM) activities in collaboration with BUMDES Desa Padaasih, West Bandung Regency to provide solutions to the problems of developing BUMDES in managing the tourism business in Curug Panganten. The BUMDES Desa Padaasih has problems that include limited village human resources related to entrepreneurial knowledge and insights for the management of BUMDES and the absence of a guide to planning the development of a tourism service business. Following up on this, Community Service activities have been carried out by the Bandung State Polytechnic by designing a Tourism Business Plan and providing Technical Guidance (BIMTEK) to administrators and activists of Padaasih Village BUMDES as partners. This activity has resulted in partners' understanding of tourism business management which includes Marketing, Business Strategy, Human Resource Management, Product Management, Technical Operational Management, and Marketing Tools and the creation of a Tourism Service Business Plan document as a guide so that BUMDES Desa Padaasih Cisarua KBB can develop a tourism business for improve the village economy.